Cost-effectiveness of precision medicine in gastrointestinal stromal tumor and gastric adenocarcinoma - Zeichner, Simon B.; Goldstein, Daniel A.; Kohn, Christine; Flowers, Christopher R. (Journal of Gastrointestinal Oncology; Vol 8, No 3 (June 23, 2017): Journal of Gastrointestinal Oncology (Novel Biologics In Era of Precision Medicine)1, 2016)
Over the past 20 years, with the incorporation of genetic sequencing and improved understanding regarding the mechanisms of cancer growth/metastasis, novel targets and their associated treatments have emerged in oncology and are now regularly incorporated into the clinical care of patients in the US. Novel, more tumor-specific, non-chemotherapy agents, including agents that are commonly used in the treatment of patients with gastric adenocarcinoma (GA) and gastrointestinal stromal tumor (GIST), fall under a broader treatment strategy, termed “precision medicine”. While diagnostic testing and associated treatments in metastatic GA (mGA) are costly and may produce marginal benefit, those associated with GIST, despite being costly, produce significant improvements in patient outcomes. Despite the significant difference in impact, the agents associated with these cancers have similar acquisition costs. In this paper, we will review the current literature regarding cost and cost-effectiveness associated with precision medicine diagnosis and treatment strategies for GA and GIST.